231k views
2 votes
Please help step by step!!!

Please help step by step!!!-example-1
User Smohadjer
by
4.8k points

2 Answers

5 votes

Answer:

-7

Explanation:

We first are going to flip the equation around.

So instead of 9 times x = -36 we'll do 36/9. 36/9 = -7.

Also you will kind of know it will be a negative number from the beginning since it's -36.

I don't know if that last part makes any sense, but I hope this helps you!

User Vyktor
by
4.7k points
4 votes


\huge \boxed{\mathfrak{Question} \downarrow}

  • What's the solution of 9 • x = - 63 ?


\large \boxed{\mathfrak{Answer \: with \: Explanation} \downarrow}


\sf \: 9 \cdot x = - 63

Divide both sides by 9.


\sf \: x=(-63)/(9) \\

Divide -63 by 9 to get -7.


\boxed{ \boxed{ \bf \: x=-7 }}

User JakeSidSmith
by
5.3k points